The effect of nursing process implementation The effect of nursing process implementation - latif Rastian, Mohammad; Borzabady Farahani, Ziba; Rasouli, Mariam; Sarbakhsh, Parvin; Niromand Zandi5, Kianosh (Advances in Nursing & Midwifery, 2015)
Background and aim : Nursing process is a deliberate problem solving approach for meeting people's health care needs .Using nursing process helps to improve the quality of patient care. The aim of this study was to determine the effect of nursing process implementation on quality of nursing care of patients hospitalized in surgical wards at Shahid Beheshty hospital in Yasuj city in 2012. Method and Material: This was a quasi- experimental study with befor-after design. The sample of the consisted of 48 nurses working in surgical wards of teaching hospitals affiliated to Yasoj Medical University. The samples were selected by using purposive sampling. The nursing care quality was evaluated by using the quality patient care scale (Qual PacS) checklist, that its validity were determined by face and content validity and its reliability was determined by using inter-observer (ICC=0.86) . Initially the nursing care quality was evaluated. Nurses participated in an educational program on nursing process and its implementation. After one month the quality of nursing care was assessed again. Data were analyzed by SPSS 16 software and using paired t-test. Results: This study showed a significant difference between the quality of nursing care in meeting psychosocial needs (p=0.031) communication needs (p=0.012), physical aspects of care (p=0.047) and the overall quality of nursing care (p=0.001) before and after implementation of nursing process. Conclusions: The results of this study showed that nursing process implementation can improve the quality of nursing care of patients in surgical wards. Keywords: Quality of nursing care, Nursing care, Nursing process.